2011
DOI: 10.1097/igc.0b013e31821cabc8
|View full text |Cite
|
Sign up to set email alerts
|

Hydronephrosis as a Prognostic Indicator of Survival in Advanced Cervix Cancer

Abstract: Hydronephrosis is an independent poor prognostic indicator of survival in patients with advanced cervical cancer. Bilateral hydronephrosis compared to unilateral involvement confers a worse overall prognosis. Additional studies are needed to determine if FIGO staging should be amended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 8 publications
3
26
0
2
Order By: Relevance
“…Survival was significantly shorter in patients with hydronephrosis (Pradhan et al, 2011). Likewise, our present study also demonstrated that hydronephrosis was associated with less survival.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Survival was significantly shorter in patients with hydronephrosis (Pradhan et al, 2011). Likewise, our present study also demonstrated that hydronephrosis was associated with less survival.…”
Section: Discussionsupporting
confidence: 71%
“…Besides medical treatment, percutaneous nephrostomy and ureteral stent placement is commonly undertaken. However, these interventions have not proven useful in prolongation of survival (Lee and Jones 1994;Pradhan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because hydronephrosis occurred at varying times during patients’ course of disease, a landmark analysis was performed at various times to assess the prognostic impact of hydronephrosis in univariate and multivariate Cox proportional hazards models. The inclusion of variables in both the logistic regression models and the Cox proportional hazards models was based on precedent in the published literature [13]. Because of the variability in approaches to cancer surveillance, cancer status was not used in the multivariate Cox proportional hazards models, although cancer stage was.…”
Section: Methodsmentioning
confidence: 99%
“…Second, previous studies report that hydronephrosis predicts compromised survival. Pradhan and others described that among 197 cervical cancer patients, hydronephrosis was associated with a statistically significant doubling of the risk for death [3]. Other investigators have reported similar prognostic outcomes in both univariate and multivariate analyses, although not consistently so [1, 2].…”
mentioning
confidence: 99%
See 1 more Smart Citation